Hubungan Reward dan Supervisi dengan Pelaksanaan Pelayanan Keperawatan Syariah - Puspitasari, Dyah Wiji; Abdurrouf, Muhammad; Yustini, Maya Dwi; Issroviatiningrum, Retno; Pramesona, Bayu Anggileo (Politeknik Kesehatan Tanjung Karang, 2020)
Reward and supervision are important parts in implementing the quality of sharia-based nursing services. The quality or quality of sharia services at RSISA is in a good category, but it takes efforts to maintain and improve continuously. One of these efforts is by increasing rewards and supervision. The purpose of this study is to analyze the relationship between reward and supervision with the implementation of sharia nursing services. The subjects of this study were inpatients at Sultan Agung Islamic Hospital Semarang with a sampling technique that is simple random sampling with 96 respondents. Data analysis techniques in this study used the Spearman correlation statistical test. The results showed that there was a relationship between reward and the implementation of sharia nursing services with a p-value of 0,05 and there was a relationship between supervision with the implementation of sharia nursing services with a p-value of 0,01. The results of this study were expected to be considered by hospital policy stakeholders to review the giving of rewards for nurses and the implementation of work supervision to nurses to improve the quality of sharia-based nursing services.